Tracking the Herd with a Shotgun — Why Do Peers Influence College Major Selection? - Michael Insler; Ahmed S. Rahman; Katherine Smith (Institute of Labor Economics (IZA), 2021)
How do peers influence people's choices? We explore this fundamental question by exploiting unique data produced by, and a natural experiment conducted on, students from the United States Naval Academy (USNA). We develop a conceptual framework to highlight that individuals can emulate others for both information (social learning) and for socializing (network externalities). We then analyze data on the preliminary preferences and ultimate major selections of USNA freshmen, exploiting a rich set of covariates and the random assignment of students to peer groups. We find that students can be influenced by peers into selecting different academic paths relative to what they would have chosen on their own. Through random reassignments of certain student groups into new peer groups, we also explore the reasons why herding occurs. The preponderance of evidence suggests that social learning, as opposed to network externalities, is the key driver for herding behavior.
Keywords: D85; I21; I23; J24; 330; major selection; peer effects; higher education; herding; social networks